2021
DOI: 10.3390/cimb43030118
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Radix Polygalae on Cognitive Decline and Depression in Estradiol Depletion Mouse Model of Menopause

Abstract: Postmenopausal syndrome refers to symptoms caused by the gradual decrease in female hormones after mid-40 years. As a target organ of estrogen, decrease in estrogen causes various changes in brain function such as a decrease in choline acetyltransferase and brain-derived neurotrophic factor; thus, postmenopausal women experience cognitive decline and more depressive symptoms than age-matched men. Radix Polygalae has been used for memory boosting and as a mood stabilizer and its components have shown neuroprote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 64 publications
0
2
0
Order By: Relevance
“…Also, RP could enhance the expression of LC3-II and Beclin1 in mouse cortex and rat prefrontal cortex (PFC), reduce the level of p62, and regulate the dysfunction of AMPK-mTOR pathway in PFC of CRS rats, thus exhibiting antidepressant effects ( Zhou et al, 2021 ). Another study found that RP significantly improved the working memory, situational memory and despair-related behaviors of estrogen-depleted mice, increased the expression of BDNF in the prefrontal cortex and the expression of BAG1 in the hippocampus, indicating that RP could improve the cognitive and depressive symptoms of postmenopausal women ( Han et al, 2021 ). However, these two studies did not systematically screen out the antidepressant metabolites in PR.…”
Section: Pharmacologymentioning
confidence: 99%
“…Also, RP could enhance the expression of LC3-II and Beclin1 in mouse cortex and rat prefrontal cortex (PFC), reduce the level of p62, and regulate the dysfunction of AMPK-mTOR pathway in PFC of CRS rats, thus exhibiting antidepressant effects ( Zhou et al, 2021 ). Another study found that RP significantly improved the working memory, situational memory and despair-related behaviors of estrogen-depleted mice, increased the expression of BDNF in the prefrontal cortex and the expression of BAG1 in the hippocampus, indicating that RP could improve the cognitive and depressive symptoms of postmenopausal women ( Han et al, 2021 ). However, these two studies did not systematically screen out the antidepressant metabolites in PR.…”
Section: Pharmacologymentioning
confidence: 99%
“…Ancient Chinese medical texts document PT’s efficacy in treating ailments such as insomnia, neurasthenia, excessive cough with phlegm, and palpitations ( Jiang et al, 2021 ; Chen et al, 2023 ). In preclinical research, PT and its extracts have demonstrated neuroprotective properties, as well as potential for dementia prevention and antidepressant effects ( Shin et al, 2018 ; Han et al, 2021 ). Traditional plant-based medicinal combinations containing PT, such as Kaixinsan ( Fu et al, 2019 ), Sagacious Confucius’ Pillow Elixir ( Hou et al, 2019 ), and Buyuan Congnao decoction ( Chen et al, 2012a ), have also exhibited pharmacological actions against AD.…”
Section: Introductionmentioning
confidence: 99%